2016
DOI: 10.5694/mja15.01103
|View full text |Cite
|
Sign up to set email alerts
|

What does “futility” mean? An empirical study of doctors' perceptions

Abstract: There is an overwhelming preference for a qualitative approach to assessing futility, which inevitably involves variability in clinical decision making. Patient benefit is at the heart of doctors' definitions of futility. Determining patient benefit requires discussing with patients and their families their values and goals as well as the burdens and benefits of further treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…These two authors (CP, CtH) iteratively discussed themes and checked for the analytical link to transcripts. 21 Then, all four authors scrutinised and discussed the data, explicitly searching for negative case analysis before refining themes. 19 Rigour was further promoted through prolonged engagement by one of the authors (CP) with the tenants over 3 years.…”
Section: Methodsmentioning
confidence: 99%
“…These two authors (CP, CtH) iteratively discussed themes and checked for the analytical link to transcripts. 21 Then, all four authors scrutinised and discussed the data, explicitly searching for negative case analysis before refining themes. 19 Rigour was further promoted through prolonged engagement by one of the authors (CP) with the tenants over 3 years.…”
Section: Methodsmentioning
confidence: 99%
“…) and our limited contact time with any one patient . However, we find that meeting the ‘gold standard’ can be aided by lists that reference the concept of ‘futility’ . There are a number of these, one example is represented in Table .…”
Section: Initiating Planning In the Patient Approaching End‐of‐lifementioning
confidence: 99%
“…15 However, we find that meeting the 'gold standard' can be aided by lists that reference the concept of 'futility'. 16 There are a number of these, one example is represented in Table 2. [17][18][19][20] Recent research has shown that the use of one such list is acceptable and reliable in the ED setting.…”
Section: Initiating Planning In the Patient Approaching End-of-lifementioning
confidence: 99%
“…This paper addresses this gap. Drawing on a larger project looking at how doctors conceptualise futile treatment,20 and the reasons they provide it,4 it reports on how doctors view the relationship between futility and resources, both conceptually and in their descriptions of their practice.…”
Section: Introductionmentioning
confidence: 99%